Stress and the Brain: An Emerging Role for Selenium - Torres, Daniel J.; Alfulaij, Naghum; Berry, Marla J. (Frontiers in Neuroscience, 2021)
The stress response is an important tool in an organism’s ability to properly respond to adverse environmental conditions in order to survive. Intense acute or chronic elevation of glucocorticoids, a class of stress hormone, can have deleterious neurological effects, however, including memory impairments and emotional disturbances. In recent years, the protective role of the antioxidant micronutrient selenium against the negative impact of externally applied stress has begun to come to light. In this review, we will discuss the effects of stress on the brain, with a focus on glucocorticoid action in the hippocampus and cerebral cortex, and emerging evidence of an ability of selenium to normalize neurological function in the context of various stress and glucocorticoid exposure paradigms in rodent models.